Coulomb excitation of exotic nuclei at REX-ISOLDE with MINIBALL - Kröll Th. (EPJ Web of Conferences, 2014)
In this contribution nuclear structure studies with post-accelerated radioactive ion beams from the REX-ISOLDE facility at CERN are presented. The method employed is γ-ray spectroscopy with the MINIBALL array following “safe” Coulomb excitation. Recent results concerning the investigation of nuclear shapes are presented and discussed.